Implementation of the Combination of Automatic Clustering and Fuzzy Time Series Models in Viewing Rice Stock Availability - sayedfachrurrazi sayed; Angga Pratama; Syukriah Syukriah; Ilham Wirayuda; Yulia Nosari (INFOKUM, 2022)
Perum bulog has an important role in supplying rice stocks, this has made Perum Bulog have to prepare a mature strategy in preparing stocks in recent years. The problem that often occurs when rice stocks cannot meet the high demand of consumers in the market causes a decrease in the available stock which results in the National Logistics Agency being unable to maintain stock availability. The second problem is the availability of very high rice stocks to meet the rice needs of the people by looking at the provision of warehousing stock. this is the most important issue for the availability of rice for the community and the State Logistics Agency is required to be able to control the supply of rice stocks. The application of fuzzy time series is used to view the stock. This will have an impact on orders that come in at the same time and in large quantities. to avoid stock shortages, which resulted in the company experiencing losses. The variables used are stock needs, the amount of stock of rice. The research methodology in data collection consists of product type data from 2018–2021 at perum bulog Aceh Utara. the set of universes of discussion U to where the fuzzy set is obtained, the minimum data is 150 and the maximum data is 2700. the number of intervals and the length of each interval of the universe set (U). linguistic sets that in the universe of speech U are A1=988, A2=1037, A3=1086, A4=1136, A5=1185, A6=1234, A7=1283. Fuzzified value from historical data Novembe 2021, 4,600, A7 and December 2019, 400 and Fuzzified A7. Fuzzy Logic Relationship (FLR) Period Dec 18 Jan 18 FLRA1 -> A6 Period Dec 19- Jan 19 A4 ->A7. forecasting and defuzzification process based on the FLRG that has been formed. Current State A1 -> 1128.42 and Current State A7 -> 1142.59. Results of Actual Data and Forecasting of Bulog Rice in North Aceh for December 2021 Actual Data of Bulog Rice Stock 1,500 Fuzzified A7 Forecasting Results 1144. error value with AFER 1.1166667% while in November 2021 while for the RMSE value 8.9442